Early age corrosion of mild steel in aggressive media - Ozturk, A.U.; Gucuyen, E.; Erdem, R.T.; Seker, S. (Фізико-хімічна механіка матеріалів, 2012)
Effect of exposure time, section type and solution concentration on mild steel early age corrosion was studied. Steel specimens section types were box, tube and corner. They were subjected to 3.5%; 5.0% and 7.0% NaCl solutions. It was established that solution concentration effects the corrosion until reaching the saturation value.